Social and technological advances for people with disabilities in Colombia (2013)
Having as a reference the work developed by the Center of Stimulation, Leveling, and Development CEDESNID for the habilitation/rehabilitation and social inclusion of the people with the condition of cognitive disability, this chapter has the purpose of doing a revision of the current status of cognitive disability in Colombia, to afterwards present the impact that can have the technological innovation in this field. For this it will be done a recount of the principal tendencies and lines of action at international level about the approach of the disability as a generality and of the cognitive/intellectual disability as a particular category. Afterwards, it will be made a revision of the most outstanding tendencies in Colombia. Finally, it will be presented the PreLingua tool as an example of the technological innovation of high social impact to be applied in the elimination of the involved barriers in the cognitive disability and as seed project for the innovation in Colombia.